Participação em grupo de promoção da saúde e qualidade de vida de idosos - Santos, Leidiene Ferreira (2014)
INTRODUCTION: the growth of the elderly population set up a worldwide phenomenon. In this scenario it is essential the establishment of strategies that consider the characteristics of old age and are aimed at maintaining the biopsychosocial health and quality of life of the elderly. Searches recommend the use of group activities as a tool that promotes learning that encourage socialization, make possible interpersonal relationships, contributes to adaptation and change in living habits of the elderly. But for that, this activity must meet the assumptions of group dynamics, ie, being implemented in response to the needs of the group members. GENERAL OBJECTIVE: to analyze the participation in group of health promotion as a strategy to improve the quality of life in elderly. METHODS: quantitative research approach, performed with elderly enrolled in a Primary Care Unit Family Health, participants (G1) and nonparticipants (G2) of group health promotion. Data were collected from june to october 2012, using an instrument with sociodemographic questions, and the WHOQOL-BREF and WHOQOL-OLD. Subsequently were entered and analyzed in software Stata version 11.0. To evaluate factors associated with QoL, were used multiple linear regression. The level of significance was set at 5 %. RESULTS: the elderly group G1 had higher mean of QoL scores in all domains of the WHOQOL-BREF, not being statistically significant only the result obtained in the psychological domain. The lowest score for the two groups, G1 and G2, in the WHOQOLBREF, was obtained in the field "environment" (G1: 60.2 ±11.2, G2: 50.5 ±12.2). The G1 group also had higher mean scores and statistically significant in facets "Past, present and future activities" (G1: 69.7, SD: 11.7, G2: 59.2, SD: 15.0) and "Social participation" (G1: 72.4 ±11.2, G2: 55.6 ±16.3). Join group was significantly associated with better QoL scores in the "physical", "social relations" and "environment" domains, and the facets "Past, present and future activities" and "Social participation”. CONCLUSION: participation in group of health promotion supports improvements to various aspects of QoL of the elderly, especially those related to social inclusion and establishment/maintenance of interpersonal relationships. Thus the group is a resource that should be used by health professionals to promote and protect the health of the elderly because it allows break situations of loneliness and gives opportunity to forge new bonds of friendship and social support networks.